2006
DOI: 10.1038/sj.eye.6702329
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Luneau SA disposable and Goldmann applanation tonometer readings

Abstract: Purpose To test the agreement of intraocular pressure (IOP) measurements made with Luneau SA applanators and Goldmann applanator. Materials and Methods A single-blind crossover trial. IOPs were measured in both eyes of subjects with both applanators. Type of applanator was alternated to eliminate systematic bias. Multiple observers were used. Observers were blind to the scale while performing measurements but not to the type of applanator used. The appearance of the meniscus was assessed semiquantitatively. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Our experiments showed that the suction forces for the two tonometers were equivalent to 0.26 and 0.19 mmHg; these values were at least one order of magnitude smaller than the differences observed clinically. Additionally, when we compared the IOP of the Goldmann and Tonojet using Bland Altman plots, we did not find a consistent underestimation by a fixed amount, which one might have expected if the suction force was solely responsible for the difference in IOP measurements [1].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Our experiments showed that the suction forces for the two tonometers were equivalent to 0.26 and 0.19 mmHg; these values were at least one order of magnitude smaller than the differences observed clinically. Additionally, when we compared the IOP of the Goldmann and Tonojet using Bland Altman plots, we did not find a consistent underestimation by a fixed amount, which one might have expected if the suction force was solely responsible for the difference in IOP measurements [1].…”
Section: Discussionmentioning
confidence: 88%
“…The tonometer is extracted past the surface of the liquid at position (d) and as it draws up a column of liquid. The force increases steadily to overcome the suction force until (e) when the column collapses and the force returns to zero at (f) 1 This is a 2% sodium hypochlorite solution. The active ingredients include sodium hypochlorite 2% w/w and sodium chloride 16.5% w/w.…”
Section: Clinical Photographsmentioning
confidence: 96%
See 1 more Smart Citation
“…In their study, they inspected the prisms prior to use and found that 14 of 189 disposable tips had to be discarded because of the presence of surface irregularities. Baddon et al [ 33 ] found that in 28 of the 140 eyes included in the study, the tonometer endpoint was difficult to assess with Luneau prisms because of excessively thick rings. The menisci endpoint was deemed to be of acceptable quality in 80% of the Luneau tip readings and 100% of the GAT readings.…”
Section: Goldmann Applanation Tonometrymentioning
confidence: 99%
“…range of 0.1-0.5 mmHg [26][27][28][29][30][31]. Studies comparing the Luneau Tonojet to reusable tip GAT found a mean IOP difference of 0.4-2.35 mmHg [26,32,33].…”
Section: Goldmann Applanation Tonometrymentioning
confidence: 99%